COMPARATIVE STUDY OF ADHESIVE STRENGTH IN MAHOGANY WOOD LAMINATED COMPOSITES - Oetama, Pandoe Satria; Sunardi, Sunardi; Ula, Shofiatul; Yusuf, Yusvardi; Dwinanto, Dwinanto; Listijorini, Erny; Santosa, Irfan (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
Adhesive technology has seen significant advancements in recent years. Compared to welding or threaded joints, adhesives provide a straightforward mechanism for joining material interfaces. Due to practicality allows for the potential development of adhesives with strengths comparable to those of traditional joints. In this study, a modified type of Polyvinyl Acetate (PVAc) adhesive was utilized as a binder for mahogany wood surfaces. The choice of PVAc adhesive is due to its common use in everyday applications, particularly in the woodworking industry. Additionally, this adhesive is relatively safe for both health and the environment. The study examined three types of adhesives: PVAc white adhesive, PVAc yellow adhesive, and a combination of the PVAc white and yellow adhesive. These adhesives were used to bond the wood surfaces, and the bond strength at the interface was evaluated through a flexural test. The results showed that the adhesive strength of white adhesive reached 111 MPa, while the mixed adhesive and yellow adhesive exhibited flexural strengths of 74.2 MPa and 63.4 MPa, respectively. Notably, the presence of white glue was found to enhance the flexural strength of mahogany wood even in the absence of adhesive.